Combination of the Simplified Modified Geneva and Wells Clinical Prediction Scoring promise a good performance in pulmonary embolism diagnosis - Çoraplı, Gökhan; Topçu, Ayşe Füsun (Journal of Surgery and Medicine, 2021)
Background/Aim: Pulmonary thromboembolism (PTE) has high mortality and morbidity, is difficult to diagnose, and is generally preventable. Clinical scoring is used for early diagnosis. Two of these often-used scoring systems include the Wells and Simplified Modified Geneva scoring systems. We aimed to comparatively determine the values of the Wells and the Simplified Modified Geneva scoring systems in showing PTE. Methods: This prospective cohort study included 195 patients who underwent computerized tomography pulmonary angiography (CTPA) with suspected PTE between May 2018 and November 2018. The Wells and Simplified Modified Geneva scores of the patients were calculated. Wells Clinical Scoring results were grouped as having a weak/strong probability of PTE, while those of the Modified Geneva clinical scoring were categorized as possible/unlikely PTE. The analyses were performed with the SPSS package 21.0 program. Results: One hundred and nine (55.9%) patients presented to the emergency department and eighty-six (44.1%) patients visited the outpatient clinic for chest diseases. Of all cases, 83 (42.6%) were male and 112 (57.4%) were female. The mean age was 57.16 (18.62) years. Forty-one (21%) patients had PTE. The sensitivity and specificity of Wells Clinical Scoring for PTE were 87.8% and 83.8%, respectively, while those of the Simplified Modified Geneva Clinical Scoring were 82.9% and 53.3%, respectively. The chi-square analysis for two clinical scorings revealed a p-value of 0.001. The negative predictive values of Wells and Simplified Modified Geneva Scores were 96.2% and 92.1%, respectively. The positive predictive value was the highest in the emergency department (80% and 39.4%, respectively). When the two clinical scores were used together, the negative and positive predictive values were 95.6% and 61.1%, respectively. Conclusion: We found that Wells Clinical Scoring is superior to the Simplified Modified Geneva Score in terms of sensitivity and specificity. The use of these two clinical scores in the outpatient clinic was more useful in excluding PT, while in the emergency department, their combination was more effective in diagnosing it.